2009
DOI: 10.1002/syn.20628
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography imaging of amphetamine‐induced dopamine release in the human cortex: A comparative evaluation of the high affinity dopamine D2/3 radiotracers [11C]FLB 457 and [11C]fallypride

Abstract: The use of PET and SPECT endogenous competition binding techniques has contributed to the understanding of the role of dopamine in several neuropsychiatric disorders. An important limitation of these imaging studies is the fact that measurements of acute changes in synaptic dopamine have been restricted to the striatum. The ligands previously used, such as [(11)C]raclopride and [(123)I]IBZM, do not provide sufficient signal to noise ratio to quantify D(2) receptors in extrastriatal areas, such as cortex, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 69 publications
7
120
0
Order By: Relevance
“…“MOR activation” was defined as the reduction in MOR binding potential from baseline to rejection or acceptance block (i.e., baseline-rejection, baseline-acceptance). This metric represents competition between radiotracer and endogenous opioids, changes in the conformational state of the receptor after activation, and/or changes in receptor concentration (e.g., via internalization, trafficking), all of which are related to endogenous opioid neurotransmission 40,41 .…”
Section: Methodsmentioning
confidence: 99%
“…“MOR activation” was defined as the reduction in MOR binding potential from baseline to rejection or acceptance block (i.e., baseline-rejection, baseline-acceptance). This metric represents competition between radiotracer and endogenous opioids, changes in the conformational state of the receptor after activation, and/or changes in receptor concentration (e.g., via internalization, trafficking), all of which are related to endogenous opioid neurotransmission 40,41 .…”
Section: Methodsmentioning
confidence: 99%
“…Measuring endogenous serotonin levels with PET is of high relevance, seeing the successful and informative implementation of such measurements in the dopaminergic system (e.g., Narendran et al 2009). It has proven difficult, though, to translate this success to the serotonergic system.…”
Section: Endogenous Serotonin Levelsmentioning
confidence: 99%
“…We reasoned that differences between patients with and without PG might be elevated when on pramipexole, since a single dose of 1 mg pramipexole has previously been shown to alter behaviour even in drug naïve individuals (Campbell-Meiklejohn et al, 2011). PET images were acquired using [11C] FLB-457, a high affinity marker used for assaying extrastriatal D2/D3 receptors (Farde et al, 1997), and which has been shown to be sensitive to endogenous DA levels in the PFC and midbrain (Montgomery et al, 2007;Narendran et al, 2009;Vandehey et al, 2010). PET scans were obtained with a high resolution PET CT, Siemens-Biograph HiRez XVI (Siemens Molecular Imaging, Knoxville, TN, U.S.A.) operating in 3D mode with an inplane resolution of approximately 4.6 mm full width at half-maximum.…”
Section: Scanning Proceduresmentioning
confidence: 99%